Toxicological evaluation of therapeutic and supra-therapeutic doses of Cellgevity® on reproductive function and biochemical indices in Wistar rats - O. Awodele; W. A. Badru; A. A. Busari; O. E. Kale; T. B. Ajayi; R. O. Udeh; P. M. Emeka (BMC, 2018)
Abstract Background The misconception about dietary supplements being safe has led many into the in-patient wards. Cellgevity® (CGV) is a Max International premiere antioxidant supplement formula used by a large population. This study evaluated the effects of therapeutic and supra-therapeutic doses of CGV on reproductive function and biochemical indices in Wistar rats. Methods Seventy-two Wistar rats weighing 130 ± 15.8 g were grouped into two categories (male or female) of six rats per group. Control group received distilled water (10 ml/kg). Others received therapeutic (14.3 mg/kg or 28.6 mg/kg) and supra-therapeutic CGV doses (1000, 2000 or 3000 mg/kg) body weight per oral respectively. Results After 60 days, supra-therapeutic doses of CGV reduced sperm motility (p < 0.05) by 31.8%, 31.3% and 34.5% respectively and increased (p < 0.05) abnormality in sperms by 200%, 241% and 141.3% respectively. CGV altered male (luteinizing, follicle stimulating hormones and testosterone) and female reproductive hormones (luteinizing, follicle stimulating hormones estrogen and progesterone) respectively. Therapeutic doses of CGV elevated reduced glutathione, superoxide dismutase, catalase and glutathione S-transferase, although, this was exceeded by supra-therapeutic doses and more in females than male rats. Supra-therapeutic dose (3000 mg/kg CGV) decreased body weight in both male and female rats by 50% (F(1.5, 30) = 1.2, p = 0.041) and 62.7% (F(2.1, 30) = 0.38, p = 0.038) respectively in treated rats. Supratherapeutic (3000 mg/kg) dose of CGV increased (p < 0.05) creatinine level by 99.1% while serum total protein was reduced (p < 0.05) by 60.1% (2000 mg/kg) and 57.2% (3000 mg/kg) respectively in male animals. In Female rats, supra-therapeutic doses of CGV elevated creatinine levels by 72.2% (1000 mg/kg), 60.2% (2000 mg/kg) and 124.8% (3000 mg/kg) respectively and 3000 mg/kg produces elevated serum low density lipoprotein by 34.6% in treated rats. Serum cholesterol, triglycerides, albumin, alkaline phosphatase were unaltered by CGV dosing. Histology shows seminiferous tubules with reduced spermatogenic cells. Also, female rat kidney revealed acute tubular necrosis at highest dose used in this study. Conclusion Overall, these data suggest that pro-oxidant potential of the supra-therapeutic CGV doses is evident. Hence, it is necessary that its administration be done with caution using appropriate doses.